Güncel istatistikler ışığında uyuşturucu veya uyarıcı madde imal ve ticareti suçu (TCK m.188) - Köse, Ahmet (My University, 2025)
TCK m. 188’de düzenlenen uyuşturucu veya uyarıcı madde imal ve ticareti suçu, hem ulusal hem de uluslararası düzeyde mücadele stratejilerinin geliştirilmesine odaklanılan suçlardan biridir. Zira, küresel ölçekte uyuşturucu veya uyarıcı madde imal ve ticareti, yasa dışı bir finans kaynağı haline gelmiş ve özellikle yasa dışı organizasyonların başvurdukları en önemli araçlardan biri olmuştur. Uyuşturucu veya uyarıcı madde imal ve ticaretinin sınırları aşan karakteri, bu suçla mücadelede yalnızca ulusal sınırlar ve hukuk sistemlerinin yetersiz kalacağını ortaya koymaktadır. Bu nedenle, ülkeler yasadışı uyuşturucu veya uyarıcı madde üretimi ve ticaretine yönelik faaliyetleri, yasalarında suç olarak tanımlayıp cezai müeyyideler getirmiştir. Uyuşturucu veya uyarıcı madde imal ve ticareti suçuyla mücadele amacıyla dünya genelinde gösterilen yoğun çabalar ve uyuşturucu talebini azaltma yönündeki artan politikalar yasa dışı madde ticaretinin giderek arttığı gerçeğini değiştirmemektedir. Bu kapsamda çalışmamızda, öncelikle uyuşturucu ve uyarıcı maddelere dair sunulacak ve devamında uyuşturucu ve uyarıcı madde çeşitlerinden, uyuşturucu ve uyarıcı maddelerle ilgili uluslararası mücadele kapsamında uluslararası örgütlerden ve uluslararası sözleşmelerden bahsedilecektir. Ayrıca, seçilen bazı ülkelerin uyuşturucu veya uyarıcı madde imal ve ticareti suçlarına ilişkin yasal düzenlemeleri ele alındıktan sonra bazı uyuşturucu ve uyarıcı maddelerin yıllara göre olay sayıları güncel istatistikler ışığında verilecektir. Ardından TCK m. 188’de suç olarak tanımlanan uyuşturucu veya uyarıcı madde imal ve ticareti suçu detaylı şekilde incelenecektir. Yine devamında uyuşturucu veya uyarıcı madde imal ve ticareti suçu ile kullanmak amacıyla uyuşturucu veya uyarıcı madde bulundurma suçu arasında temel farklar yüksek yargı kararları ışığında ele alınıp incelenecektir. Sonuç kısmında ise, söz konusu suçla mücadelede önemli olduğu düşünülen çeşitli çözüm önerileri ile çıkarımlar sunulacaktır.

The crime of manufacturing and trafficking in narcotic or psychoactive substances, regulated under Article 188 of the Turkish Penal Code, is one of the offenses that focus on the development of both national and international strategies to combat it. This is because, on a global scale, the production and trafficking of narcotics or psychoactive substances have become an illegal source of finance and, particularly, one of the main tools used by illegal organizations. The transnational nature of drug manufacturing and trafficking reveals that national borders and legal systems alone are insufficient in combating this crime. Therefore, countries have defined activities related to the illegal production and trafficking of narcotic or psychoactive substances as crimes in their laws and have imposed criminal penalties. Despite the intense global efforts to combat the crime of drug manufacturing and trafficking, and the increasing policies aimed at reducing drug demand, the growing reality of illegal drug trade remains unchanged. In this context, our study will first provide general information about narcotic and psychoactive substances, followed by a discussion of the different types of these substances. It will then address international efforts to combat drug and psychoactive substance trafficking, focusing on international organizations and treaties. After examining the legal regulations concerning the crime of manufacturing and trafficking narcotic or psychoactive substances in selected countries, the study will present updated statistics on the number of incidents related to specific narcotics and psychoactive substances over the years. Next, the crime of manufacturing and trafficking in narcotic or psychoactive substances, as defined in Article 188 of the Turkish Penal Code, will be examined in detail. Furthermore, the fundamental differences between the crimes of drug manufacturing and trafficking and the possession of narcotic or psychoactive substances for personal use will be analyzed, with reference to key judicial decisions. In the conclusion section, various proposed solutions and conclusions deemed significant in the fight against this crime will be presented.
The crıme of manufacturıng and traffıckıng narkotıc or stımulant substances (Article 188 of the Turkish penal code) in light of currenet statistics
Keywords: Drugs of abuse; hukuk; law; Law and legislation; Narcotics and crime; Turkey; Türkiye; Uyuşturucular; Uyuşturucular ve suç; Yasa ve yasama